Spatial perception of whole-body orientation depends on gymnasts' expertise - Heinen, T.; Walter, N.; Hennig, L.; Jeraj, D. (Science of Gymnastics Journal, 2018)
The perception of spatial orientation of the body is a fundamental process in the precise performance of complex motor tasks, such as those found in acrobatic sports. While visual information is thought to be an important informational source when performing gymnastics skills, it is still questionable, which role visual information plays in the perception of spatial orientation in matters of gymnastics expertise and task specificity. Thus, this study targets the question, which role visual information plays in the perception of spatial orientation as a function of specific task demands and gymnastics expertise. High-skilled and low-skilled gymnasts were compared in their estimation of body tilt while being rotated about the transverse axis and the anterior-posterior axis in a human gyroscope with either full visual information available or occluded visual information. Results revealed that high-skilled gymnasts exhibited a better estimation of body tilt as compared to low-skilled gymnasts. Estimated tilt angles varied as a function of rotation axis and expertise, but not as a function of visual information. It was concluded that an increased spatial orientation ability may result from an increased sensitivity in individual sensory systems, and/or from an optimized processing of interacting sensory information that is specific to gymnasts` experience with particular motor tasks and the corresponding task demands.